The effects of an imagery intervention on implicit and explicit exercise attitudes. (March 2015) - Markland, David; Hall, Craig R.; Duncan, Lindsay R.; Simatovic, Jacqueline
Abstract: Objectives: This study examined the effects of exercise imagery on implicit and explicit attitudes towards exercise and the moderating effect of exercise status. It was predicted that exercise imagery would activate a pattern of positive automatic associations with exercise that would be reflected in more positive implicit attitudes. Corresponding effects were expected for explicit affective attitudes, but imagery was not expected to influence explicit instrumental attitudes. Design: A post-test only comparison group design. Method: Participants ( N  = 160; 40 male and 40 female frequent exercisers, 40 male and 40 female less frequent exercisers) were randomly allocated, stratified by exercise status and gender, to undergo either guided imagery of a pleasant experience of exercising or a comparison imagery condition. Participants then completed an Implicit Association Test, measures of explicit affective and instrumental attitudes, and an imagery manipulation check. Results: There were significant main effects for experimental condition and exercise status on implicit attitudes, with more positive attitudes in the exercise imagery condition and for more frequent exercisers. There were significant main effects for exercise status on explicit affective and instrumental attitudes. Exercise status did not moderate the effects of imagery on implicit or explicit attitudes. Conclusion: This is the first study to demonstrate that implicit attitudes to exercise can be modified, although only immediate effects were assessed. Future research should assess the generalisability of the findings in less active populations and examine the effects of repeated imagery on implicit attitudes to determine whether it could have more lasting effects and impact on actual exercise behaviour. Highlights: We examined the effects of exercise imagery on implicit and explicit attitudes to exercise. Guided imagery of a pleasant experience of exercising was compared to a control imagery condition. Exercise imagery led to more positive implicit attitudes to exercise. Exercise imagery had no effect on explicit attitudes. This is the first study to demonstrate that implicit attitudes to exercise can be modified.